Evaluation of Saussurea costus Nanoparticles in the Treatment of Periodontitis: Impact on NF-κB and TNF-α Expression - Moelyanto, Azzahra Salsabila Adira; Arundina, Ira; Budhy, Theresia Indah; Surboyo, Meircurius Dwi Condro; Oki, Aqsa Sjuhada; Ming, Cheng Hwee (European Journal of Dentistry, 2025)
Porphyromonas gingivalis is a major contributing pathogen in periodontitis and triggers an inflammatory response that leads to tissue damage, primarily through the activation of proinflammatory cytokines such as nuclear factor kappa B (NF-κB) and tumor necrosis factor-α (TNF-α). Saussurea costus, a medicinal plant known for its anti-inflammatory properties, offers a potential alternative to prevent inflammation. This study explores the effects of S. costus nanoparticles on inflammation in periodontitis, specifically examining their ability to reduce the expression of NF-κB and TNF-α.Twenty male Wistar rats were injected with P. gingivalis into the central incisor region of the mandible to induce periodontitis. The rats were then treated with S. costus nanoparticles, alongside a control group. Immunohistochemical staining was performed to assess the expression of NF-κB and TNF-α at two time points: 2 and 5 days posttreatment. Bone and lower anterior gingival sulcus tissues were analyzed for immunohistochemical expression of these markers.Statistical analysis was performed using the Kruskal–Wallis and Mann–Whitney U tests.Treatment with S. costus nanoparticles resulted in significantly lower expressions of NF-κB and TNF-α compared with the control group at both 2 and 5 days posttreatment (p < 0.05).The S. costus nanoparticles effectively reduced NF-κB and TNF-α expression in periodontitis, with a more pronounced effect observed on day 5 compared with day 2, suggesting its potential as a therapeutic agent in managing periodontal inflammation.
Keywords: nanoparticles; Saussurea costus; NF-κB; TNF-α; inflammation